Chondroblastoma of the Clivus: Case Report and Review - Liu, Jonathan; Ahmadpour, Arjang; Bewley, Arnaud F.; Lechpammer, Mirna; Bobinski, Matthew; Shahlaie, Kiarash (Journal of Neurological Surgery Reports, 2015)
Background and Importance Chondroblastoma is a benign primary bone tumor that typically develops in the epiphyses of long bones. Chondroblastoma of the craniofacial skeleton is extremely rare, with most cases occurring in the squamosal portion of the temporal bone. In this report, we describe the first case of chondroblastoma of the clivus presenting with cranial neuropathy that was treated with endoscopic endonasal resection. We review the literature on craniofacial chondroblastomas with particular emphasis on extratemporal lesions.Case Presentation A 27-year-old woman presented with severe headache, left facial dysesthesias, and diplopia. Physical examination revealed hypesthesia in the left maxillary nerve dermatome, and complete left abducens nerve palsy. Imaging demonstrated an expansile intraosseous mass originating in the upper clivus with extension superiorly into the sella turcica and laterally to involve the medial wall of the left cavernous sinus. The tumor was completely resected via an endoscopic endonasal approach, with postoperative improvement in lateral gaze palsy. Histopathology was consistent with chondroblastoma.Conclusion Chondroblastoma is a rare tumor of the craniofacial skeleton that should be included in the differential diagnosis of an osteolytic lesion of the clivus. Complete surgical resection remains the mainstay of treatment.
Keywords: chondroblastoma; clivus; endoscopic endonasal approach; clival tumor